Development of metarhizium anisopliae as a mycoinsecticide: from isolation to field performance - Tupe, Santosh G.; Pathan, Ejaj K.; Deshpande, Mukund V. (Jove-Journal of Visualized Experiments, 2017)
A major concern when developing commercial mycoinsecticides is the kill speed compared to that of chemical insecticides. Therefore, isolation and screening for the selection of a fast-acting, highly virulent entomopathogenic fungus are important steps. Entomopathogenic fungi, such as Metarhizium, Beauveria, and Nomurea, which act by contact, are better suited than Bacillus thuringiensis or nucleopolyhedrosis virus (NPV), which must be ingested by the insect pest. In the present work, we isolated 68 Metarhizium strains from infected insects using a soil dilution and bait method. The isolates were identified by the amplification and sequencing of the ITS1-5.8S-ITS2 and 26S rDNA region. The most virulent strain of Metarhizium anisopliae was selected based on the median lethal concentration (LC50) and time (LT50) obtained in insect bioassays against III-instar larvae of Helicoverpa armigera. The mass production of spores by the selected strain was carried out with solid-state fermentation (SSF) using rice as a substrate for 14 days. Spores were extracted from the sporulated biomass using 0.1% tween-80, and different formulations of the spores were prepared. Field trials of the formulations for the control of an H. armigera infestation in pigeon peas were carried out by randomized block design. The infestation control levels obtained with oil and aqueous formulations (78.0% and 70.9%, respectively) were better than the 63.4% obtained with chemical pesticide.